"The Pyrenees are not hollow": the mountain as a boundary object "Os Pirineus não são ecos": a montanha como objeto de fronteira - Jérôme Lamy (História, Ciências, Saúde: Manguinhos, 2009)
In Toulouse, around 1850, a controversy about the structure of the Pyrenees pitted observatory director Frederic Petit against geology professor Alexandre Leymerie. The object of the debate was an assumption formulated by Petit: that the inside of the Pyrenees was practically hollow. This proposal was based on work that Petit initiated in order to determine the latitude of Toulouse. The debates, which took place within the Toulouse Academy of Science and also in local newspapers, illustrate the organization of disciplinary spaces in the nineteenth century. Petit defended his research method based on calculation; the geologist's perspective was from the field. The emergence of the less mathematical science of geology came up against nineteenth-century astronomical practices, centered on calculation. Dissected by calculation or by visual observation, the mountain was an object of controversy from the perspective of distinct scientific practices. Em Toulouse, por volta de 1850, uma controvérsia sobre a estrutura dos Pirineus colocou o diretor do Observatório, Frederic Petit, contra o professor de geologia Alexandre Leymerie. O motivo do debate foi a hipótese formulada por Petit: o interior dos Pirineus era praticamente oco. A proposição baseava-se no trabalho que Petit iniciara para determinar a latitude de Toulouse. Os debates, que tiveram lugar na Academia de Ciências de Toulouse e também em periódicos locais, ilustram a organização dos espaços disciplinares no século XIX. Petit defendia seu método de pesquisa baseado em cálculos; a perspectiva do geólogo provinha do campo. A emergência da ciência geológica, menos matemática, vinha de encontro às práticas da astronomia daquele século. Analisada por cálculos ou pela observação visual, a montanha foi um objeto de controvérsia entre diferentes práticas científicas.